2011
DOI: 10.1007/s00464-011-1677-2
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-technique for single-incision pediatric endosurgical pyloromyotomy

Abstract: The Cross-technique appears superior to standard SIPES pyloromyotomy and should be preferentially used for single-incision endosurgical pyloromyotomy for hypertrophic pyloric stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
7
0
4
Order By: Relevance
“…We and others have described the technique of crossing 2 straight instruments in performing SILS in children to keep the surgeon's hands apart, minimize clashing of instruments, avoid the laparoscopic view parallel with the working instruments, and allow intracorporeal maneuverability comparable to CL. 12,[23][24][25] However, the operating surgeon needs to get accustomed to the new ergonomics where the left-handed instrument is on the right side of the operative field and vice versa. We have recently demonstrated in video manuscripts that the crossed-instruments technique is not that counter-intuitive as it may sound, even in complex urological ablative procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have described the technique of crossing 2 straight instruments in performing SILS in children to keep the surgeon's hands apart, minimize clashing of instruments, avoid the laparoscopic view parallel with the working instruments, and allow intracorporeal maneuverability comparable to CL. 12,[23][24][25] However, the operating surgeon needs to get accustomed to the new ergonomics where the left-handed instrument is on the right side of the operative field and vice versa. We have recently demonstrated in video manuscripts that the crossed-instruments technique is not that counter-intuitive as it may sound, even in complex urological ablative procedures.…”
Section: Discussionmentioning
confidence: 99%
“…1-10); a second period (period II), could be called "consolidation period" (case nos. [11][12][13][14][15][16][17][18][19][20], and a third period (period III), as an "improvement period" (starting from case no. 21).…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, laparoscopic pyloromyotomy (LPM) had been introduced as an alternative method by Alain et al 10 Originally recorded observations and experiences emphasized the difficulty of this procedure, the longer operative time, and the higher incidence of intra-and postoperative complications. [11][12][13] Currently, the literature points out the same efficiency of the laparoscopic approach compared with laparotomy. LPM is described as safe as laparotomy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Yuri, et al reported reviewing single incision surgery in a pediatric patient and proposed the nomenclature 'single incision pediatric endosurgery' (SIPES). In the literature, they reported SIPES applied to neonates and patients under 12 months of age [2,[7][8][9]. Numerous studies have address the feasibility of single incisions.…”
Section: Discussionmentioning
confidence: 99%